A critical multimodal analysis of gender representation in South Africa and Nigeria English language school textbooks - Biowe, Oluchi Maureen (My University, 2020)
This interpretative mixed methods study applied a critical multimodal literacy framework to holistically examine how multiple modes were utilised to represent gender in South African and Nigerian English language school textbooks. Two current and widely used English language textbooks were selected from both countries to investigate how males and females have been represented. Adapting content analysis categories from Porreca (1984), Hartman and Judd (1978),including Kress and Van Leeuwen’s (2006) social semiotic approach to multimodal analysis, a critical hybrid analytical model was designed for this study. Findings revealed that generally, both textbooks represented males and females stereotypically, however the degree of stereotype and bias between the two textbooks vary. In both the linguistic and visual modes of the textbooks males were numerically represented more than their female counterparts; female firstness was numerically insignificant when compared to the frequency of male firstness; and males and females were portrayed in traditional stereotypical occupational roles and activities. In addition, males were represented in more high status professional occupation than females. Both genders were described as having specific character traits that positioned males as brave and females as passive. Nonetheless, evidence of some subtle differences between both textbooks suggests that the South African textbook Solutions for All adopts a more gender sensitive and balanced representation than the Nigerian textbook Junior English Project. Furthermore, the multimodally designed contents of the two textbooks were explored to discover how gender has been represented in relation to power, positioning and subjectivities, including the ways in which the textbooks pedagogises texts in relation to the activities and exercises accompanying the multimodal textbooks. The exploration showed that both textbooks employed a number of modes ,and drew on discourses of power relations and subject positions to represent each gender differently, thereby reproducing patriarchal gendered ideologies that positioned males as more successful, prominent and powerful than females
A research report submitted in partial fulfilment of the requirements for the degree of Masters in Education by coursework and research report, School of Education, University of Witwatersrand, 2020
Keywords: Modality (Linguistics); Language and sex-Study and teaching